Perceived Usefulness of KALAM - Ali, Z.; Ismail, R.; Abu Bakar, A. H.; Muhammad, N. N.; Ahmad Azmey, F. L. (Novelty Journals, 2019)
The use of educational technology immersed rapidly in higher institutions. Learning Management System (LMS) is one the most popular educational technology system used in learning process. This study sought to identify the students’ perceived usefulness of using KALAM and to determine the significant differences between genders with respect to their perceived usefulness of using KALAM in language learning. Data from online questionnaires were collected from 90 respondents who took English course. This study used descriptive and inferential (t-test) statistics to analysis the data. Hence, the findings proved that students’ perception on the usefulness of KALAM in language learning was positive. Several implications of these findings were also discussed.